A Hybrid Heuristic Harmony Search Algorithm for the Vehicle Routing Problem With Time Windows - Yang Zhang; Jiacheng Li (IEEE Access, 2024)
In this paper, we present a hybrid heuristic method based on the harmonic search algorithm to solve the vehicle routing problem with time windows. The importance of efficient path planning in logistics and supply chain management is emphasized herein, particularly under complex constraints like time window and vehicle capacity limits. The hybrid heuristic harmony search algorithm combines the global search capability of the harmony search algorithm with the accuracy of the local search heuristic to efficiently explore and harness the solution space. Through rigorous testing on the Solomon dataset, the hybrid heuristic harmony search algorithm performed remarkably in the generation of competitive solutions while maintaining the computational efficiency of the solutions. The results showed that the algorithm achieved competitive solutions even under strict time window constraints. The convergence of the algorithm was examined, and its strong performance in handling complex instances was revealed. This study enhances the operational efficiency of an organization and provides perspectives and solutions for optimization strategies in the domains of logistics and supply chain management.